Drug Utilization Evaluation of Carbapenems in a Teaching Hospital in Tabriz-Iran - Taher Entezari-Maleki; Nooshin Ebrahimi; Zhinous Bayatmakoo; Haleh Rezaee (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: Carbapenems are beta-lactam antibiotics with broad-spectrum activity for Gram-positive, Gram-negative and anaerobic bacteria and have become the antibiotics of last resort for many serious bacterial infections. The irrational use of carbapenems (imipenem or meropenm) has increased the risk of multi-drug resistant pathogens. The aim of this study was to evaluate the pattern of carbapenem utilization within 9 months and measure compliance with references in Imam Reza Hospital, Tabriz, Iran. Methods: During 9 months, 100 patients who received carbapenems randomly get selected under the supervision of the attending physician in Imam Reza Hospital affiliated to the Tabriz university of Medical sciences. After coordination with supervisor of each ward, the necessary information was extracted and American Hospital Formulary System (AHFS) and UpToDate 21.3 references were used to assess appropriate indication and accurate dosage of carbapenems. Results:: The most common cause of prescribing was lower respiratory tract infection (29%). Carbapenems were prescribed for 64% of patients as an appropriate indication. The dose of carbapenems was correct in 74% of patients and duration of carbapenems therapy was correct in 84% of cases. Dose readjustment was necessary for 28 patients, although for 25 of whom it was performed. Only 19 patients had positive culture results. Conclusion: Despite the global guidelines, carbapenem consumption in health care systems is incorrect. So, comprehensive programs for rational drug use in all medical centers conducted by a clinical pharmacist seems necessary to be employed.